Onde está Tereza?: a “presença” da mulher negra no livro didático - SENNA, Daniela de Oliveira (2018)
The silence of the fountains falls on the black woman. Historiography has, for the most part, concealed the most relevant female actions by restricting itself to citing some simpler facts and placing women, in general and in particular, women in black, rather than subordination, that is, in the rear of the men or waiting for them. This historical construction materializes in the representations present in the textbook, an instrument so widespread in Brazilian schools. In this sense, one of the objectives of this work is to understand how the black woman has been approached in the didactic book of History (LDH). It expresses a body of ideas and perceptions that are current in society and the academic milieu, it is a far-reaching pedagogical instrument that has been disputed by diverse fields of knowledge, in which the presence of the woman is subsumed, the black woman is practically invisible. However, the importance that it acquires in school daily life is evident, constituting a pedagogical tool of great breadth and scope, which in itself represents a positive gain. However, it does require updates and, perhaps, support. In this sense, and in a propositional way, we sought the construction of a complementary pedagogical resource, the comic strips.